Dinamika Kinerja Keuangan Sektor Kelapa Sawit: Pengaruh Modal Kerja, Likuiditas, dan Struktur Modal terhadap Profitabilitas - Almahdi, Wili Husain; Fitriasuri, Fitriasuri; Noviardy, Andrian; Widyanti, Yeni (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to examine the effect of Working Capital Turnover (WCTO), Cash Turnover, Cash Ratio, and Debt to Equity Ratio (DER) on profitability, as measured by the Net Profit Margin (NPM), in palm oil plantation companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Profitability is a key indicator of financial performance, especially in industries heavily reliant on operational efficiency and working capital management. This study employs a quantitative method using multiple linear regression analysis. The sample consists of 12 palm oil companies selected through purposive sampling. The results reveal that Cash Turnover and DER have a significant effect on profitability, while WCTO and Cash Ratio do not have a significant individual impact. However, all four variables jointly have a significant effect on profitability. These findings suggest that companies must optimize their working capital efficiency and maintain a balanced capital structure to enhance financial performance.